Pressure relief of nonideal mixtures: Composition trajectories and residue curve maps. Issue 1 (5th October 2020) - Dillon, Paul
Abstract: During the course of a pressure relief discharge from a vessel containing a multicomponent liquid mixture, composition changes occur that affect the properties of the vessel contents. In this work, a model of the dynamic relief process for ternary, nonideal, homogeneous mixtures is developed, under the assumption of vapor‐only venting. Opening/reclosing of the relief valve introduces state‐events, which require reinitialization of the model at each state transition. The relationship between the pressure relief model and the concept of residue curves, which describe simple‐distillation processes, is demonstrated. It is known that the presence of azeotropes and distillation boundaries in mixtures restricts the composition trajectories of simple‐distillation processes, as well as continuous distillation columns at total reflux. In this work, the residue‐curve analogy is extended to vapor‐only pressure‐relief, where vapor composition changes directly affect the operation of the pressure‐relief device. Examples of dynamic relief processes are developed for ternary mixtures with varying nonideality.